The Importance of Family Emotional Support for Adherence to Taking Diabetic Medication in Elderly People with Diabetes Mellitus: Pentingnya Dukungan Emosional Keluarga terhadap Kepatuhan Minum Obat Diabetik pada Lansia Diabetes Mellitus - Pangastuti, Tri Endah; Riyanti, Eska; Yardes, Nelly; Nurdahlia, Nurdahlia (Politeknik Kesehatan Kemenkes RI Jakarta I, 2024)
Diabetes mellitus is a public health problem that is of concern to both developed and even developing countries because one in two elderly people suffer from diabetes mellitus. Chronic hyperglycemia in synergy with other metabolic abnormalities in diabetes mellitus patients can cause damage to multiple organ systems, leading to the development of disabling and life-threatening health complications, microvascular (retinopathy, nephropathy, and neuropathy) and macrovascular complications. The level of patient compliance in taking medication is one of the factors that determines the success of diabetes mellitus therapy. This study aims to determine the emotional support of the family on the level of adherence to taking diabetes medication in elderly people with diabetes mellitus. The sample in this study was 86 people using a non-probability sampling technique with a consecutive sampling approach. The research design used was descriptive correlation with a cross-sectional approach. The data analysis test used is univariate, bivariate with the Chi Square test. The research results show that there is a significant relationship between family emotional support and adherence to taking diabetes medication in elderly people with diabetes mellitus (p=0.001). Conclusion: Family emotional support for patients is very necessary for compliance to achieve successful diabetes mellitus therapy so that it indirectly plays a role in stabilizing blood glucose levels in diabetes mellitus patients.